Efficacy of subsequent therapies in patients with advanced ovarian cancer who relapse after first-line olaparib maintenance: results of the PAOLA-1/ENGOT-ov25 trial - Harter, P.; Marth, C.; Mouret-Reynier, M. A.; Cropet, C.; Lorusso, D.; Guerra-Alía, E. M.; Matsumoto, T.; Vergote, I.; Colombo, N.; Mäenpää, J.; Lebreton, C.; de Gregorio, N.; et al. (Annals of Oncology, 2025)
Background: The use of first-line poly(ADP-ribose) polymerase (PARP) inhibitor maintenance therapy is increasing in advanced ovarian cancer. Understanding the efficacy of first subsequent therapy (FST) in patients experiencing disease progression in the first-line setting is important to optimize postprogression treatments. We evaluated the efficacy of FST in patients from PAOLA-1/ENGOT-ov25 (NCT02477644) who received first-line olaparib maintenance. Patients and methods: This post hoc analysis evaluated the efficacy of subsequent chemotherapy following disease progression by assessing time from FST to second subsequent therapy (SST) according to whether progression occurred during versus after first-line olaparib maintenance and FST type. A multivariate Cox model was used in the olaparib plus bevacizumab arm to identify prognostic factors influencing the efficacy of subsequent chemotherapy. Results: Of 806 randomized patients, 544 (67.5%) progressed and received subsequent chemotherapy. The median time from FST to SST was shorter in patients in the olaparib plus bevacizumab arm who progressed during first-line olaparib maintenance (6.1 months) than in those who progressed after first-line olaparib maintenance (11.4 months). Multivariate analysis indicated that progression after (versus during) first-line olaparib maintenance influenced time from FST to SST (hazard ratio 0.65, 95% confidence interval 0.50-0.84; P = 0.0011) independently of platinum-free interval or clinical risk. Among patients who progressed and received platinum-based chemotherapy with a PARP inhibitor as FST, the efficacy of subsequent therapies was also dependent on whether progression occurred during versus after first-line olaparib maintenance. Conclusions: These results suggest that the timing of disease progression relative to first-line olaparib maintenance may impact the efficacy of subsequent platinum-based chemotherapy. Although results should be interpreted with caution, across all subgroups, including patients who received platinum-based chemotherapy with PARP inhibitor rechallenge as FST, the median time from FST to SST was longer if progression occurred after versus during first-line olaparib maintenance.
CRIS-Team Scopus Importer:2025-02-04
Keywords: first subsequent therapy; olaparib; ovarian cancer; PAOLA-1/ENGOT-ov25; PARP inhibitor; rechallenge